Evaluation of Geotechnical Parameters using Geophysical Data - Adewoyin, Olusegun; Joshua, Emmanuel Oluwagbemi; Akinwumi, Idowu Isaac; Omeje, Maxwell; Joel, Emmanuel Sunday (ITB Journal Publisher, LPPM ITB, 2017)
The financial implications and the time required for carrying out a comprehensive geotechnical investigation to characterize a site can discourage prospective private residential building developers, especially where a large area of land is to be investigated for construction purposes. Also, most of the geotechnical test procedures utilized during site investigation only provide information on points tested in the subsurface. This research method suggests an approach of investigating the subsurface condition of a site in order to obtain key subsoil geotechnical properties necessary for foundation design for proposed engineering facilities. Seismic wave velocities generated from near surface refraction were combined with percussion drilling and cone penetration tests to obtain a comprehensive geotechnical investigation. From the results of the seismic refraction method, the bulk density of the soil, Youngâs modulus, bulk modulus, shear modulus and allowable bearing capacity of a competent layer that can bear structural load at the particular study site were determined. The most competent layer was found within the depth observed by geotechnical methods. In addition, regression equations were developed in order to directly obtain the bulk density of the soil, Youngâs modulus, bulk modulus, shear modulus and allowable bearing capacity from the primary wave velocities.